Vaccination with a Leishmania infantum HSP70-II null mutant confers long-term protective immunity against Leishmania major infection in two mice models. - José Carlos Solana; Laura Ramírez; Laura Corvo; Camila Indiani de Oliveira; Manoel Barral-Netto; José María Requena; Salvador Iborra; Manuel Soto (Public Library of Science (PLoS), 2017)
The immunization with genetically attenuated Leishmania cell lines has been associated to the induction of memory and effector T cell responses against Leishmania able to control subsequent challenges. A Leishmania infantum null mutant for the HSP70-II genes has been described, possessing a non-virulent phenotype.The L. infantum attenuated parasites (LiΔHSP70-II) were inoculated in BALB/c (intravenously and subcutaneously) and C57BL/6 (subcutaneously) mice. An asymptomatic infection was generated and parasites diminished progressively to become undetectable in most of the analyzed organs. However, inoculation resulted in the long-term induction of parasite specific IFN-γ responses able to control the disease caused by a challenge of L. major infective promastigotes. BALB/c susceptible mice showed very low lesion development and a drastic decrease in parasite burdens in the lymph nodes draining the site of infection and internal organs. C57BL/6 mice did not show clinical manifestation of disease, correlated to the rapid migration of Leishmania specific IFN-γ producing T cells to the site of infection.Inoculation of the LiΔHSP70-II attenuated line activates mammalian immune system for inducing moderate pro-inflammatory responses. These responses are able to confer long-term protection in mice against the infection of L. major virulent parasites.